PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MELALUI CONTEXTUAL TEACHING and LEARNING BERBASIS SEJARAH LOKAL PADA SISWA SEKOLAH DASAR - Rijal, Ibnu; Ani Rosidah; Ari Yanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the difference in students' problem-solving abilities after implementing Contextual Teaching and Learning (CTL) based on local history in IPAS learning on the topic of Stories About My Region. This quantitative study employed a pre-experimental method with a one-group pretest-posttest design. The participants were 28 fourth-grade students at SDN Cicenang 1. Data were collected using a problem-solving ability test administered before and after the implementation of the learning approach. Data analysis included descriptive statistics, normality testing, homogeneity testing, and a paired sample t-test. The descriptive analysis showed an increase in the mean score from 62.68 on the pre-test to 73.75 on the post-test, representing an improvement of 11.07 points. The minimum score increased from 17 to 39, while the maximum score increased from 94 to 100. The paired sample t-test resulted in a t-value of -2.563 with 27 degrees of freedom and a significance value of 0.016 < 0.05. Therefore, there was a statistically significant difference in students' problem-solving abilities before and after the implementation of local-history-based CTL. These findings indicate that local-history-based CTL can serve as an alternative approach to IPAS learning by connecting instructional content with students' environment and experiences, thereby supporting the development of problem-solving abilities in elementary school.